Job Satisfaction In Generation Y Employees At Swiss-Belresort Pecatu - Putra, I Kadek Pramana (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This study examines job satisfaction among Generation Y employees at Swiss-Belresort Pecatu, motivated by concerns about high turnover rates and varying levels of engagement within this demographic. The research aims to identify the factors influencing job satisfaction and analyze how demographic variables affect satisfaction levels. A quantitative research method was employed, utilizing a survey distributed to Generation Y employees at the resort. Data were analyzed using descriptive statistics and regression analysis to explore relationships between satisfaction levels and influencing factors such as work environment, company policies, career development opportunities, and work-life balance. The results indicate that while the overall job satisfaction of Generation Y employees is moderate, key factors such as career growth opportunities and work-life balance significantly impact their satisfaction. Differences in satisfaction levels were also found based on demographic variables, including age, gender, education, and length of service. The study concludes that Swiss-Belresort Pecatu should adopt tailored strategies to address the specific needs of Generation Y employees, focusing on career development, improved work-life balance, and a supportive work environment. These findings provide valuable insights for the management to enhance employee satisfaction and retention, ensuring a motivated and productive workforce in a competitive hospitality industry.